Designer landscapes for sustainable biofuels - Koh, L.P.; Levang, P.; Ghazoul, J. (2009)
Oil palm is one of the most extensively cultivated biodiesel feedstocks worldwide, and expansion of its cultivation poses a significant threat to ecosystems, biodiversity and potentially the global climate. We evaluate the prospects of land sparing and wildlife-friendly farming, two contrasting approaches for reducing the impacts of oil palm agriculture. We draw on concepts from both approaches to suggest more sustainable production systems and argue that landscapes under threat from oil palm expansion need to be designed in recognition of biodiversity, economic and livelihood needs. Specifically, we advocate agroforestry zones between high conservation value areas and intensive oil palm plantations to create a more heterogeneous landscape benefiting both biodiversity and rural communities. Similar principles could apply to biofuel systems elsewhere.